WHAT IT MEANS TO BE A WOMAN:An Analysis Of "A Woman's Life" By Rachel Billington Within The Perspectives Postfeminism and Popular Culture - Ida Hidayah, - (2012)
The research entitled "What it means to be a woman: An Analysis of "A Woman's Life" By Rachel Billington Within the Perspectives of Postfeminist and Popular Culture" aims to investigate how Postfeminist Perspective and Popular Culture are reflected through the three women characters in the novel. A qualitative descriptive method with textual analysis approach help to interpret and to understand the complex textual descriptions of how people experince, that is behaviours, beliefs, opinions, emotions and relationship of individual. The study is framed within Postfeminist Perspective argued by Stephanie Genz to analyze the textual evidences from the novel A Woman's Life written by Rachel Billington. The novel itself belongs to the Popular Literature that illustrates the female experiences in women's literature which can be read within Postfeminist Perspective. It is found that through the construction of the three women characters, backlash is represented through the three women characters to maintain their desires of having great achievement in public sphere and live a happy life with their couples. Backlash in Postfeminism is influenced by the Popular Culture in form of media-inspired images which relates to how a woman to a good self-presentation. To maintain their desires, the three women characters celebrate themselves through lifestyle and fashion to have good self-presentation and to be desired by men.